Arbitrage Opportunities in the Klibor Futures Market in Malaysia - Shahbudin, Shakirah (2006)
A futures contract is an agreement to buy or sell an asset at a future date at a price agreed upon today. The Kuala Lumpur Interbank Offered Rate (“KLIBOR”) futures or known as FKB3 is the interest rate futures contract available in Malaysia. This study examines the availability of arbitrage opportunities after accounting for transaction costs for interest rate futures contract. Fair value of the KLIBOR futures price is calculated using Implied Forward Rate and is compared to the actual price to determine the arbitrage opportunities from 1996 to 2003. The pricing of the KLIBOR futures contract is said to be efficient when the mispricing between fair value and actual value is small, if not zero. When mispricing is small, the benefit will spill over to the hedgers, whereby they can make a more effective hedging decision. The findings show that mispricing is small for contracts near to maturity and it increases as the contracts move further from maturity. This suggests that arbitrage opportunities are available to be exploited for contracts furthest from maturity. It also suggests that hedging decision can be made effectively if one trades in contracts near to maturity. More concerted efforts should be in place to encourage domestic and foreign retailers as well as foreign institutions to trade in KLIBOR futures contract. To provide liquidity in the interest rate futures market, Market Makers’ Scheme should be reintroduced. The finding also shows that the difference is narrowing between the actual price and the fair price of interest rate futures contracts as a function of time to maturity.